INOVASI PELAYANAN PUBLIK PADA KANTOR SAMSAT KOTA TEGAL (STUDI KASUS PADA PAJAK KENDARAAN BERMOTOR) - Gayuh Sih Suwastiti; Endang Larasati; Sundarso Sundarso; Titik Djumiarti (Journal of Public Policy and Management Review, 2016)
In order to reach good governance, a government must constantly initiate an innovation. Tegal One Roof System, in regards to achieving good governance, innovates on motor vehicle tax by applying technology-based assessment through online system. However, there are still a number of people who are lack of information about this facility. Furthermore, there is still network/data center problems, middleman/broker, and unmet qualification of the workers. The aim of this research was to analyze innovation of public service in One Roof System of Tegal. Qualitative-descriptive method is employed to depict actual conditions. Data was collected through observation, interview, and photo-taking. Componential Analysis was comprised of relative advantage, compatibility, complexity, trialability, and observability. The result showed that there are still uninformed civilians regarding this online One Roof System Public Service, network/data center problems, middleman/broker, and unmet qualification and shortage of number of the workers, and data input problem. It is suggested that Tegal One Roof System publish its existence of, do repairment on the network system, hire extra workers, upgrade current workers’ qualification, and hold information technology training to its operator. Government is suggested to adopt Tegal online One Roof System in order to enhance its public service.